A report on the DataCite Summer 2013 Meeting. Issue 1 (25th February 2014) - C. Jantz, Ronald
Abstract : Purpose: – The purpose of this conference report is to highlight the key points in the DataCite Summer 2013 Meeting. Design/methodology/approach: – The approach provides a summary of each presentation in the DataCite Summer Meeting. Findings: – The DataCite 2013 Meeting demonstrated that there are many stakeholders engaged in the data citation and reuse mission and that much progress has been made in the past year. Originality/value: – This brief summary provides highlights of the conference that are not easily gleaned from the posted online slides.